2014
DOI: 10.1117/12.2039318
|View full text |Cite
|
Sign up to set email alerts
|

A novel method for single bacteria identification by Raman spectroscopy

Abstract: In this paper we present results on single bacteria rapid identification obtained with a low-cost and compact Raman spectrometer. At present, we demonstrate that a 1 minute procedure, including the localization of single bacterium, is sufficient to acquire comprehensive Raman spectrum in the range of 600 to 3300 cm -1 . Localization and detection of single bacteria is performed by means of lensfree imaging over a large field of view of 24 mm 2 . An excitation source of 532 nm and 30 mW illuminates single bacte… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2016
2016
2018
2018

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(2 citation statements)
references
References 20 publications
0
2
0
Order By: Relevance
“…Thus, it is now possible to do mass spectrometric analysis of several hundred metabolites, with dense coverage of primary metabolism, in complex biological extracts and at throughputs of >1000 samples per day and the process can also be directed to specific target like enzyme activity [278,279]. The recent Advances in Infrared and Raman spectroscopy are also helpful in the rapid and low cost differentiation, identification and metabolome characterization of microbial strains [280,281]. Zhao et al [282] studied FT-IR spectra of Micromonospora strains isolated from coastal sediments and found that this method can be applied to indicate in which environmental isolates have been cultured previously.…”
Section: Metabolomics-based Approaches For Secondary Metabolite Discomentioning
confidence: 99%
“…Thus, it is now possible to do mass spectrometric analysis of several hundred metabolites, with dense coverage of primary metabolism, in complex biological extracts and at throughputs of >1000 samples per day and the process can also be directed to specific target like enzyme activity [278,279]. The recent Advances in Infrared and Raman spectroscopy are also helpful in the rapid and low cost differentiation, identification and metabolome characterization of microbial strains [280,281]. Zhao et al [282] studied FT-IR spectra of Micromonospora strains isolated from coastal sediments and found that this method can be applied to indicate in which environmental isolates have been cultured previously.…”
Section: Metabolomics-based Approaches For Secondary Metabolite Discomentioning
confidence: 99%
“…Raman spectroscopy has been evaluated as a potential technology platform for a reagent-less environmental monitoring system (Ronningen and Bartko, 2009 ; National Academy of Sciences, 2013 ; Kusić et al, 2014 ; Schultz et al, 2014 ; Zhou et al, 2014 ; Baritaux et al, 2015 ; Hlaing et al, 2016 ; Stöckel et al, 2016 ; Gao et al, 2017 ; Lorenz et al, 2017 ). This approach relies on the notion that target biological agents exhibit reproducible Raman profiles that are sufficiently distinct from the profiles of material routinely observed in aerosols, enabling triage of aerosol samples (i.e., discrimination of “suspect” aerosol samples from a large volume of non-relevant samples).…”
Section: Introductionmentioning
confidence: 99%